Upaya Guru PAI dalam Meningkatkan Minat Belajar Baca Tulis Al Qur’an di SMAN 1 Juwana Pati - Kamto, Kamto (AL-BURHAN, 2023)
This study aims to determine the efforts of Islamic Religious Education teachers in increasing interest in learning to read and write the Qur'an at SMAN 1 Juwana and to determine the supporting and inhibiting faktors. The type of research is a case study with a descriptive qualitative approach. The primary sources are Islamic Religious Education teachers and students, while secondary data are literature studies and supporting documents. Data collection techniques are in-depth interviews, observations, and document studies. Analysis techniques are data reduction, data presentation, and conclusions or data verification. The results of the study show that the efforts made by Islamic Religious Education teachers in increasing interest in learning to read and write the Qur'an at SMAN 1 Juwana are by taking a personal approach, conducting learning activities to read and write the Qur'an with a variety of learning methods, using existing technology such as LCD projectors, Al-Qur'an reading and writing applications, and other supporting technologies as well as applications such as "Learn Quran Tajwid" and Al-Qur'an learning videos are very helpful in attracting student interest. Supporting faktors in addition to the professional ability of teachers, the ability to manage classes, also the availability of reading books and sufficient references from the library, involving parents in the learning process strengthens support at home, teacher role models and a comfortable learning environment. Inhibiting faktors are the lack of initial student abilities, and unsupportive family environment.Keywords: Islamic Religious Education Teachers, interest in learning, reading and writing the Qur'an